Mariology, Anthropology, Synergy and Grace: Why Is Luther So Far Apart from Cabasilas? - Panagiotis Kantartzis (Religions, 2021)
The issue of “Mariology” is one that divides the Eastern Orthodox and the Evangelical Christians. In this paper we are approaching the issue through the juxtaposition and comparison of the three Mariological sermons of Nicholas Cabasilas, on the one hand, with Martin Luther’s Commentary on the Magnificat, on the other. The study of the two works side by side will bring to surface the theological presuppositions which explain the differences between the Eastern Orthodox and the Evangelical views. It will also help us identify some key points that need further discussion and clarification but also ways to reach a point of mutual agreement and understanding.